A case of secondary acute myeloid leukemia on a background of glycogen storage disease with chronic neutropenia treated with granulocyte colony stimulating factor. Issue 1 (23rd July 2019) - Khalaf, Dina; Bell, Heather; Dale, David; Gupta, Vikas; Faghfoury, Hanna; Morel, Chantal F.; Tierens, Anne; Weinstein, David A.; Yan, Jiong; Thyagu, Santhosh; Maze, Dawn
Abstract: Congenital neutropenias due to mutations in ELANE, SBDS or HAX1 or in the setting of glycogen storage disease (GSD) which is caused by SLC37A4 mutation, often require prolonged granulocyte colony stimulating factor (G‐CSF) therapy to prevent recurrent infections and hospital admission. There has been emerging evidence that prolonged exposure to G‐CSF in cases with congenital neutropenia other than GSD is associated with transformation to myelodysplastic syndrome/acute myeloid leukemia.